The snowball fight - Ferry, Beth (Clarion Books, 2025)
One wintry morning, the snow begins and so does . . . a snowball fight! In her signature verse, Beth Ferry recounts a day spent behind snowbanks and on sleds, while Tom Lichtenheld's cinematic art delights readers with sly and snowy twists.